10,000 Nos - Del Negro, Matthew (Ascent Audio, 2021)
10,000 NOs: How to Overcome Rejection on the Way to Your YES chronicles actor Matthew Del Negro's tough journey from humble beginnings, through a sea of rejections, on the way to his eventual rise to become a recognizable face on some of history's most acclaimed television shows. Along the way, he learned hard lessons about perseverance, persistence, and resilience. Teaching listeners how to make it through the tough times and deal with massive uncertainty by retaining the flexibility to change course and pivot to follow your passion, Del Negro explains how to achieve success in even the most competitive industries. The book, which delves into his personal story from Division I athlete to his professional dream of becoming an actor without any show business connections, shares the wisdom and knowledge Del Negro has gained from both his failures and successes in one of America's most competitive industries: professional acting. Amidst his own stories from life and acting, Del Negro weaves anecdotes and quotes from interviews he has had with a wide range of inspirational people from all walks of life on his popular podcast, 10,000 NOs. The list of high-achievers includes professional athletes, bestselling authors, Forbes list entrepreneurs, cancer survivors, Hollywood elite, and more.